Three-dimensional ready-to-pick reservoir-based preconcentrator with a pillar-structured channel for miRNA applications - Lee, Seungmin; Kim, Jinhwan; Lee, Na Eun; Kim, Kang Hyeon; Park, Seong Jun; Park, Jeong Soo; Kim, Cheonjung; Hong, Ji Hye; Yoon, Dae Sung; Yoo, Yong Kyoung; Lee, Jeong Hoon (Frontiers in Sensors, 2022)
A sample preconcentration technique that exceeds a microfluidic device’s limited processing volume (up to microliters) is critical for real sample pretreatment applications. Here, we have developed a 3D-printed preconcentrator with a pillar structure (3DP2) to enrich the biological samples up to hundreds of microliter scales (700 μL) within 20 min by utilizing ion concentration polarization (ICP). We designed three-dimensional ready-to-pick reservoirs serially connected with a pillar-structured channel to enable large-volume preconcentration by balancing the preconcentrating forces (depletion, electrophoretic, and electroosmotic force) generated by ICP. Using the I-t and I-V curves, we confirmed that ICP performance was enhanced due to a pillar structure’s suppression of the vortex. Finally, we preconcentrated bovine serum albumin (BSA) and micro ribonucleic acid-21 (miRNA-21) two-fold. Moreover, depending on their size and charge, these were concentrated at different locations and could be extracted easily using pipettes. We believe that this study provides a novel strategy for downstream applications.